Diseño de un Modelo de Gestión Financiera para la Maximización de Utilidades y Minimización de Costos para la Empresa Textilera Kidz Manía ubicada en la ciudad de Atuntaqui - Ríos Núñez, Miguel Ángel (2015)
The purpose of this research is to propose a model of financial management that maximizes profits and reduce costs, this proposal has focused mainly on the behavior of the accounts of assets and current liabilities which are the determinants of working capital , with which seeks to contribute to the company to achieve a higher position in the market with the implementation of competitive strategy by implementing the financial model allows to improve profitability and competitive in the industry. To fulfill the objectives were determined three strands of research development ; on this basis it can be mentioned that Chapter I refers to the theoretical and methodological bases that will sustain the proposal; back to it in Chapter II , there has been gathering information in order to get the current situation of the company in the management of its assets and liabilities ; and finally in Chapter III , has established a specific proposal for the Company Kidz Mania , with which you can optimize profits.